When adults without university education search the Internet for health information: The roles of Internet-specific epistemic beliefs and a source evaluation intervention. (July 2015) - Kammerer, Yvonne; Amann, Dorena G.; Gerjets, Peter
Highlights: General Internet beliefs and two types of justification beliefs examined. Differential relationships with navigation behavior and post-search decisions found. Positive effects of source evaluation intervention on navigation behavior. Positive effects of source evaluation intervention on post-search decisions. The intervention strengthened beliefs concerning justification by multiple sources. Abstract: In the present research, N = 48 adults without university education were tasked to conduct two web searches on unfamiliar health-related issues. Three research objectives were examined: the predictive value of individuals' Internet-specific epistemic beliefs for their navigation behavior and post-search decisions in Web Search Task 1; the effects of a short source evaluation intervention on individuals' navigation behavior and post-search decisions in Web Search Task 2; and the effects of the source evaluation intervention on individuals' Internet-specific epistemic beliefs. Results showed that beliefs concerning the justification by multiple sources were positively related to the time spent on reliable objective web pages and to the likelihood to make a post-search decision that was in accordance with the objective pages. Beliefs that the Internet is a reliable knowledge resource were also positively related to the time spent on objective pages as well as to greater certainty in the post-search decision. Second, in Web Search Task 2, the intervention group spent more time on objective web pages, was more likely to make a decision that was in accordance with these pages, and was more certain of their decision than the control group. Third, one week after the intervention, individuals possessed stronger beliefs concerning the justification by multiple sources than before. In conclusion, the present research indicates that both adaptive Internet-specific beliefs and a short source evaluation intervention have positive effects on non-university educated adults' online health information seeking and that their Internet-specific epistemic beliefs can be fostered through such an intervention.